Alaina Monteil: capstone - Monteil, Alaina, artist (Colorado State University. Libraries, 2025)
The artist's statement: A lot of my inspiration for art comes from watching my children grown and seeing them figure out this world around them. Their curiosity and excitement, even for the smallest things, helps me view my surroundings diﬀerently. Coming from a job in atmospheric science and gaining new inspiration from my little ones, my digital art has a very nature based approach. I'm able to create images, whether through photography or diﬀerent programs, then edit with a computer which allows me to make it as realistic or as fanciful as I want. The scientific side of my art is full of research focused on creating beautiful images that represent phenomena centered around my interest in nature. The other portion of my work, I aim to create something that is meaningful on an emotional level that has such an impact, people can relate through their own lives, connecting them to my art. I’m exploring a dialogue between human presence and the natural world around us, hoping that my work helps us all wonder what it truly means to be human in this ecosystem.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art